Brand identity factors : developing a successful Islamic brand - Alihodzic, Vedad (Anchor Academic Pub., 2013)
Hauptbeschreibung The market for Islam-compliant products is getting more and more important, due to the high impact of religious obligation on Muslim consumer behaviour. According to studies, the market for Muslim-compliant brands has increased dramatically, with a global worth of 1.5 trillion a year. However, the market for Islam-compliant brands seems to be underdeveloped in Europe when compared to the rest of the world. Surprisingly, little research is conducted in this highly attractive segment, although Islam is assumed to be the fastest growing religion, with a total of 1.6.